RANCANG BANGUN PRONY BRAKE DYNAMOMETER UNTUK PENGUJIAN ENGINE MOBIL HEMAT ENERGI TIM JOGOPATI - Prabuditya Bhisma Wisnu Wardhana; Angga Fahad Musthofa; Agung Fauzi Hanafi; Asmar Finali; Rochmad Eko P.U. (Jurnal Inovasi Teknologi Manufaktur, Energi dan Otomotif, 2025)
This research aims to determine the force required by the Prony Brake Dynamometer, understand the manufacturing process, and analyze the test results, to ensure this tool can measure engine performance accurately and efficiently. This research includes the design, manufacture and calibration of the Prony Brake Dynamometer, followed by energy efficient car engine testing. The data obtained is analyzed to evaluate the performance of the dynamometer and engine performance, to ensure that this tool can be used accurately and efficiently in testing. The force required to press the caliper piston to the Disc Brake is 136.2 N. The input power with a current of 2.4 A is obtained of 264 W. braking force Fb from the 2.4 Current variation with Ft 0.3 kg is 0.98 N. The power (P) output of the electric motor using the 2.4 Current variation with F scale of 0.3 m and rpm 1473 is 14.2833 watts. It takes a pressing force of 136.2 N on the brake shoes to test a torque of 10.3 Nm at a rotational speed of 3600 rpm. The output power at a rotational speed of 1473 rpm is 14.28 W with a measured input power of 264 W. Meanwhile, at a rotational speed of 1435 rpm the output power produced is 120.61 W with a measured input power of 572 W. Keyword : design, prony brake, dynamometer, engine